EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF JIGSAW DALAM MENINGKATKAN PARTISIPASI SISWA KELAS IIIA PADA MATA PELAJARAN PELAJARAN PENDIDIKAN PANCASILA DI SD - Santhi, Puja Adithia; Sadtyadi, Hesti; Sudarto, Sudarto (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2025)
Student participation plays an important role in achieving the desired learning objectives. This study aims to determine the effectiveness of the jigsaw cooperative learning model in increasing the participation of class IIIA students in Pancasila education subjects at SDN 7 Wonogiri. This study uses Classroom Action Research (CAR) with a mixed method approach that combines qualitative and quantitative approaches which are implemented for 2 cycles within a period of four weeks. The subjects of this study were 28 students in class IIIA. Data collection techniques used observation, interviews, questionnaires and pre-tests and post-tests to measure student participation and understanding during the learning process. The results of the study showed an increase in student participation in the observation results which were initially 67.5% with a moderate category in cycle I then increased to 81.25% with a good category in cycle II. In addition, the N-Gain analysis showed an increase in understanding of the material from the moderate category (0,48) to high (0,80). This model not only increases participation but also student learning outcomes significantly. The conclusion in this study is that the jigsaw cooperative learning model is effective in increasing the participation of class IIIA students in Pancasila education subjects at SDN 7 Wonogiri. ABSTRAKPartisipasi siswa memiliki peranan yang penting bagi ketercapaian keberhasilan tujuan pembelajaran yang diinginkan. Penelitian ini bertujuan untuk mengetahui efektivitas model pembelajaran kooperatif jigsaw dalam meningkatkan partisipasi siswa kelas IIIA pada mata pelajaran pendidikan Pancasila di SDN 7 Wonogiri. Penelitian ini menggunakan Penelitian Tindakan Kelas (PTK) dengan pendekatan mixed method yang menggabungkan pendekatan kualitatif dan kuantitatif yang dilaksanakan selama 2 siklus dalam kurun waktu empat minggu. Subjek penelitian ini adalah 28 siswa yang kelas IIIA. Teknik pengumpulan data menggunakan observasi, wawancara, angket serta pre-test dan post-test untuk mengukur partisipasi dan pemahaman siswa selama mengikuti proses pembelajaran. Hasil penelitian menunjukkan peningkatan partisipasi siswa pada hasil observasi yang awalnya 67,5% dengan kategori sedang pada siklus I kemudian meningkat menjadi 81,25% dengan kategori baik pada siklus II. Selain itu analisis N-Gain menunjukkan peningkatan pemahaman materi dari kategori sedang (0,48) menjadi tinggi (0,80). Model ini tidak hanya meningkatkan partisipasi melainkan juga hasil belajar siswa secara signifikan.Simpulan dalam penelitian ini bahwa model pembelajaran kooperatif jigsaw efektif dalam meningkatkan partisipasi siswa kelas IIIA pada mata pelajaran pendidikan Pancasila di SDN 7 Wonogiri.